RESULTS SECOND YEAR OF THE PROJECT "IVOŠ" - Milan, KLEMENT (Trends in education, 2010)
The article presents the results and outputs of activities undertaken within the second year of the project Ivoš - improving the quality of education by introducing interactive teaching in schools, which is funded by the European Social Fund and the Czech state budget.
Keywords: interactive whiteboards; project activities; systematic training; lessons; interactive lessons.